Building commitment in Malaysia public service:some conceptual issues and considerations - Zin Razali Mat
Emphasising critically of commitment of public servants in developing democracies for faster development, the author focusses on the concept of commitment, critically examining the relationship of the public service to work, organisations, governance, community and citizens in Malaysia. To him, prospects for maintaining andd enhancing employee commitment in public service in Malaysia are not very encouraging due to problems both in the current environment of public agencies and in the border society as well. Howerver, to remedy it, he discusses some conceptual views and approaches that can build opportunities for developing and maintaing a public work force committed to the community it serves.
Keywords: Civil Service -- Malaysia; Civil Service